2010
DOI: 10.1108/00907321011020734
|View full text |Cite
|
Sign up to set email alerts
|

Reference service without the desk

Abstract: Purpose -This article aims to describe how a college library critically examined its maintenance of a traditional reference desk for in-person services and changed its service model to suit local needs. Design/methodology/approach -The author examined quantitative and qualitative reference use data prior to changing the service model, and the purpose of reference services was formally articulated. Following the change the author again examined use data, conducted a convenience sample survey, and measured visit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 4 publications
0
29
0
Order By: Relevance
“…Library users often assume anyone behind a public service desk is a librarian and as Arndt (2010) observed, if student workers staff the desk when the librarians are out this further confuses the patron. Additionally, Hernon and Pastine (1977) and Fagan (2003) supported this in their research, finding that no difference was made between professional librarians and clerical staff.…”
Section: Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…Library users often assume anyone behind a public service desk is a librarian and as Arndt (2010) observed, if student workers staff the desk when the librarians are out this further confuses the patron. Additionally, Hernon and Pastine (1977) and Fagan (2003) supported this in their research, finding that no difference was made between professional librarians and clerical staff.…”
Section: Literature Reviewmentioning
confidence: 95%
“…With the complex definition and perception of the term "reference" and the variety of roles that a librarian fills it follows that terminology and services could be confusing to library users (Arndt, 2010). Based on anecdotal evidence and the library literature, the Regis Reference Services Department already suspected that many of their users did not have a clear understanding of the librarian's role and services offered within the library, but they needed more evidence to support a change.…”
Section: Introductionmentioning
confidence: 99%
“…Some writers argue that reference service should be phased out altogether. 5 In recent years, libraries have eliminated reference desks, 6 reinstated them, 7 and created merged service points. 8 Many have added texting and instant messaging or "chat" reference to their service mix; at the same time, other libraries are reporting surprisingly low preference for or use of such services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…What is lacking from these analyses is a comprehensive look at any aspect of reference services in the liberal arts. The research that does exist on liberal arts reference frequently takes the form of case studies at specific libraries (Arndt, 2010;Faix, 2014;Faix et al, 2010) . They were chosen as a sample group because they were easy both to identify as liberal arts colleges and to get in touch with.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The value of tradition and institutional considerations clearly mean different things to different libraries: some librarians believe they support a blending of reference with other services or a shift to an appointment model while others see the existence of a reference desk as critical for a liberal arts college. The "symbolic value" of having a reference desk echoes Arndt (2010). She remarked that this was a definite concern when Dickinson College closed its desk, but in spite of this, Dickinson (an Oberlin Group institution) did close its desk and found that it was better for it.…”
Section: When We Went From a Reference Desk To A Consultation Area Wementioning
confidence: 99%